Peranan Dinas Tenaga Kerja dan Perindustrian dalam Meningkatkan Kesempatan Kerja Bagi Penyandang Disabilitas - Husna Fitria Arzul; Afriva Khaidir; Adil Mubarak (Journal of Education on Social Science (JESS), 2019)
The purpose of this study is to explain the role of the Department of Labor and Industry in Padang City in increasing employment opportunities for persons with disabilities. This research is a qualitative research using descriptive methods. Data in this study were obtained from observation, interviews, and documentation studies. The validity test of the data in this study is the method of triangulation method. Based on the results of research and discussion, it was found that the role of the Department of Labor and Industry in Padang City in increasing employment opportunities for persons with disabilities in policy management was still limited to providing skills training and recommending persons with disabilities to companies. employment, in financial management is budgeting in accordance with the RAB, in information management in the form of submission of information on job vacancies, and in the management of external relations has not been implemented properly because there has been no collaboration with providers of employment.